Therapeutic efficacy of multiple intravenous infusions of anti-tumor necrosis factor alpha monoclonal antibody combined with low-dose weekly methotrexate in rheumatoid arthritis. - Maini, R; Breedveld, F; Kalden, JR; Smolen, J; Davis, D; Macfarlane, J; Antoni, C; Leeb, B; Elliott, M; Woody, J; Schaible, T; Feldmann, M (1998)
OBJECTIVE: To evaluate the efficacy, pharmacokinetics, immunogenicity, and safety of multiple infusions of a chimeric monoclonal anti-tumor necrosis factor alpha antibody (cA2) (infliximab; Remicade, Centocor, Malvern, PA) given alone or in combination with low-dose methotrexate (MTX) in rheumatoid arthritis (RA) patients. METHODS: In a 26-week, double-blind, placebo-controlled, multicenter trial, 101 patients with active RA exhibiting an incomplete response or flare of disease activity while receiving low-dose MTX were randomized to 1 of 7 groups of 14-15 patients each. The patients received either intravenous cA2 at 1, 3, or 10 mg/kg, with or without MTX 7.5 mg/week, or intravenous placebo plus MTX 7.5 mg/week at weeks 0, 2, 6, 10, and 14 and were followed up through week 26. RESULTS: Approximately 60% of patients receiving cA2 at 3 or 10 mg/kg with or without MTX achieved the 20% Paulus criteria for response to treatment, for a median duration of 10.4 to >18.1 weeks (P < 0.001 versus placebo). Patients receiving cA2 at 1 mg/kg without MTX became unresponsive to repeated infusions of cA2 (median duration 2.6 weeks; P=0.126 versus placebo). However, coadministration of cA2 at 1 mg/kg with MTX appeared to be synergistic, prolonging the duration of the 20% response in >60% of patients to a median of 16.5 weeks (P < 0.001 versus placebo; P=0.006 versus no MTX) and the 50% response to 12.2 weeks (P < 0.001 versus placebo; P=0.002 versus no MTX). Patients receiving placebo infusions plus suboptimal low-dose MTX continued to have active disease, with a Paulus response lasting a median of 0 weeks. A 70-90% reduction in the swollen joint count, tender joint count, and C-reactive protein level was maintained for the entire 26 weeks in patients receiving 10 mg/kg of cA2 with MTX. In general, treatment was well tolerated and stable blood levels of cA2 were achieved in all groups, except for the group receiving 1 mg/kg of cA2 alone, at which dosage antibodies to cA2 were observed in approximately 50% of the patients. CONCLUSION: Multiple infusions of cA2 were effective and well tolerated, with the best results occurring at 3 and 10 mg/kg either alone or in combination with MTX in approximately 60% of patients with active RA despite therapy with low-dose MTX. When cA2 at 1 mg/kg was given with low-dose MTX, synergy was observed. The results of the trial provide a strategy for further evaluation of the efficacy and safety of longer-term treatment with cA2.